(untitled) (Bangladesh Journal of Medical Biochemistry, 2024)
Ovarian cancer is one of the commonest cancers in gynecology with very high fatality to case ratio. In approximately 70% of all cases of ovarian cancers, the disease is not diagnosed before reaching an advanced stage. Thus early diagnosis of ovarian malignant tumor becomes a key factor in improving the survival rate of patients. This study was aimed to evaluate HE4 (Human Epididymis 4) biomarker for the diagnosis of ovarian malignancy in admitted patients with pelvic mass of ovarian origin scheduled for surgery from Obstetrics and Gynecology department of different medical colleges of Dhaka city and Bangabandhu Sheikh Mujib Medical University (BSMMU). It was a cross-sectional analytical study carried out by non-probability sampling. For this study, 110 admitted patients with ovarian tumor scheduled for surgery were selected.Purpose and procedure of the study was explained in details and informed written consent was taken from all the study subjects before collection of blood sample. Clinical information was taken from the patients’ hospital notes. Before surgery serum HE4 was measured and after surgery, histopathology reports were collected for each patient.Depending on histopathology reports, patients were categorized as benign and malignant. Diagnostic efficacy of HE4 was evaluated with respect to sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and likelihood ratios considering histopathology report as gold standard. To evaluate the performance of HE4 based on optimal cut-off (34.3 pmol/L), we found better sensitivity, NPV and satisfactory likelihood ratios but low specificity and PPV compared to suggested cut-off. The findings of this study shows that HE4 is not a useful biomarker to help in the assessment and management of patients with suspected ovarian cancer. Bangladesh J Med Biochem 2019; 12(1): 11-15